UNILATERAL CANCELLATION OF SHARIA INSURANCE POLICIES: JUDICIAL ANALYSIS FROM MAQASHID SHARIA PERSPECTIVE - Vidya Nurchaliza; Nur Chanifah; Siti Rohmah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research analyzes the judicial considerations in Court Decision Number 2030/Pdt.G/2024/PA.JS concerning unilateral cancellation of sharia insurance policies from a maqashid sharia perspective. The Islamic finance industry in Indonesia has experienced rapid growth, particularly in the sharia insurance sector. However, policy cancellation practices often create imbalances between insurance companies and policyholders. Article 251 of the Commercial Code (KUHD), which previously regulated unilateral cancellation rights, was revoked by Constitutional Court Decision Number 83/PUU-XXII/2024, creating a legal vacuum. Using a normative juridical approach with statute, case, and conceptual approaches, this study examines primary legal materials including legislation, court decisions, and DSN-MUI fatwas, as well as secondary materials from legal literature and journals. The research reveals that judicial considerations in the analyzed decision reflect efforts to harmonize positive law with maqashid sharia principles, emphasizing the importance of distinguishing between intentional and unintentional violations in accordance with Islamic justice principles. The study proposes a cancellation mechanism based on maqashid sharia incorporating violation classification, proportional sanctions, clarification opportunities, transparent procedures, and sharia-based alternative dispute resolution. This mechanism aims to realize the principles of hifzh al-mal (property protection), 'adl (justice), tawazun (balance), and maslahah 'ammah (general welfare) in sharia insurance practices